AC dielectric properties of antimony‑germanate‑borate optical glass rods co‑doped with silver nanoparticles - Boiko, Oleksandr; Żmojda, Jacek Mariusz; Kochanowicz, Marcin; Ragiń, Tomasz; Markiewicz, Jakub; Markowski, Krzysztof; Komarzyniec, Grzegorz Karol (Archives of Electrical Engineering (Online), 2025)
The article presents the investigation of the AC dielectric properties of optical glass rods co-doped with Ag nanoparticles. The samples presented a molar composition of 20Sb2O3–30GeO2–(45 – x )H3BO3–5Al2O3–xAg and differed with Ag concentration x in the range of 0.1 mol.%-0.6 mol.% as well as geometric dimensions. The rods have been prepared by the standard melt-quenching technique. An impedance spectroscopy in the measurement frequency range of 4 Hz–8 MHz at room temperature was used to determine the dielectric properties of rods. The paper shows frequency characteristics for impedance, phase shift angle, resistance, conductivity, dissipation factor, and both components of permittivity. The samples demonstrate high resistance (4.4 x 106 < R < 2.0 x 1011 Ω) and mostly negative phase shift angle (0 < θ ≤ –90°), which indicates the purely dielectric nature of the materials and their capacitive character. Introducing Ag NPs into the rod’s structure causes growth in the impedance of about 40–120%, amplifies the real part of the per-mittivity over fivefold, and increases the electrical conductivity from two to 4.5 times, de-pending on frequency f. Resistance, conductivity, dissipation factor, and imaginary part of permittivity demonstrate two-step saddle-shape dependencies that reflect dielectric and conduction processes between non- or partly oxidized or fully oxidized Ag nanoparticles separated by a glass matrix. The saddle points are different for low and high frequency regions, the values of which are next to 500 Hz and 5 x 105 Hz, respectively, referring to two relaxation times in the interphase polarization process. Hopping conductivity has been proposed as the charge transfer mechanism in nanocomposite rods.